A historical overview of water quality in the coastal seas of China - Xin, Ming; Sun, Xia; Xie, Lin-Ping; Wang, Bao-Dong (Frontiers in Marine Science, 2023)
Using historical data, long-term variations in pollutant sources and water quality in China’s coastal waters over the last three decades are reviewed. The results show that the total area of non-clean water, which reflects state of total water quality, increased rapidly before 2000, but then underwent two stages of decline, with a modest decline by one-quarter between 2001 and 2015, followed by a sharp decline of more than half of that in 2015 since then. Consequently, water quality at present is better than it was at the beginning of the 1990s. The total area of polluted water fluctuated without any trend from the end of the 1990s until 2015, but has declined sharply by nearly two-thirds since 2015, indicating that the water quality in China’s coastal seas has improved substantially. Geographically, the Bohai Sea was the first to see a turning point in water quality, followed by the Yellow Sea and East China Sea, while the South China Sea was the last. The main pollutants that govern the water quality grade and area are dissolved inorganic nitrogen and phosphate as well as petroleum hydrocarbons. As a response to variations in water quality, changes in both the frequency and total area affected by harmful algal blooms were similar to those of water quality over the last three decades, albeit with a slight lag. Analysis showed that variations in water quality were closely related to the land- and sea-sourced pollutant inputs. The combination of shift in the mode of economic growth from high-speed growth to high-quality development and the enforcement of the new, strictest ever Environmental Protection Law resulted in a significant decline of pollutant emissions, inducing a turning point in the water quality in the coastal seas of China in the mid-2010s.